Shape optimization method of grid shell structures based on PGSA - Shi, Kairong; Lin, Jinlong; Jiang, Zhengrong; Chen, Runyang (Journal of constructional steel research, 2025)
Aiming at the structural shape optimization of grid shell structures, PGSA (plant growth simulation algorithm) is firstly introduced to the field of structural shape optimization. Based on the basic principle of PGSA, a novel shape optimization method of grid shell structures based on improved GSL&PS-PGSA (growth space limitation & parallel search) is proposed. The corresponding structural optimization process is given, and the optimization programs are compiled by MATLAB and the APDL (ANSYS Parametric Design Language). The shape optimization examples of typical grid shell structures are analyzed by the proposed method. The results show that the proposed shape optimization method based on improved GSL&PS-PGSA can effectively explore rational structure form, improve mechanical properties of the structure, and reduce structure sensitivity to geometric defects. As a result, it provides a new approach for shape optimization of grid shell structures. •In this paper, PGSA algorithm is first introduced into the field of spatial structure shape optimization.•This paper uses MATLAB and ANSYS secondary development language APDL to compile the optimization program, and gives the detailed program running diagram and explanation.•The optimization method proposed in this paper is applied to different types of spatial structure shape optimization problems, and it is analyzed to prove that the method has wide applicability and better optimization effect.